Development of Product and Marketing Strategies for Cashew Nuts Products of the Community Along the Lamsebok Economic Geography Route, Ubon Ratchathani Province - Ratree, Umarin; Chaiyasat, Chatchadapon; Chinchaisrirapat, Walaipun (Arts of Management Journal, 2024)
This article aimed to study: 1) the operating capabilities of the communities; 2) product development, product branding, and packaging of cashew nut products; and 3) marketing strategies for cashew nut products from the communities within the Lamsebok geographical economic route in Ubon Ratchathani province. This research is mixed-methods research. The research conducted in-depth group interviews to collect qualitative data with community members and representatives from government agencies, totaling 62 individuals. Content analysis and weighted scores were used for collecting qualitative data. Then, product development was evaluated using a questionnaire collected from consumers in Ubon Ratchathani province. The sample group wasn't determined based on probability. Instead, They were randomly selected, amounting to 400 people. Data analysis used descriptive statistics, including percentage, mean, and standard deviation. The research results are as follows: 1) The operating capabilities of the communities using PRIMO-F analysis and PEST analysis models received weighted scores for internal operations at a good level (3.67) and external environmental conditions at a moderate level (3.38). 2) The overall prototype product development has gotten an average (4.06) at a high level. The product branding reflects the value of the product received an average (3.91) at a high level. Packaging with beautiful and appealing patterns has an average (3.86) at a high level. 3) Marketing strategies using the TOWS Matrix technique and determining indicators with the Balance Scorecard found that the marketing tactics that need to be expedited are finding creative methods to produce unique products, developing recipes for processing cashew nuts in other differentiated forms, and promoting the brand for more recognition among consumers, which includes promoting in both online and offline media outlets.